Main reasons for buying through an ecommerce - Infante Plaza, Angel; Vidal Fernández, Pablo (mktDESCUBRE; Vol 1 No 21 (2023): Twenty-first Edition (January - June)DO - 10.36779/mktdescubre.v1i21.816, 2023)
In Ecuador, online shopping through e-commerce has experienced significant growth in recent years. This can be attributed to the increasing use of technology and the convenience and benefits of online purchasing. As a result, many companies selling products now offer this option to their customers as an additional sales channel. This study aims to explore the main reasons for purchases made through e-commerce, specifically focusing on the December 2022 period, particularly during the holiday season. A quantitative and descriptive research methodology was employed, utilizing a survey administered to a sample of 150 individuals located in the city of Guayaquil who made purchases through e-commerce during the specified time period. Additionally, a documentary research approach was complemented with other related studies on the topic. The research analysis determined that the primary reason for purchase was time-saving, accounting for 36% of responses, followed by offers and promotions at 26%. As an additional finding, the highest frequency of purchases ranged from 2 to 5 products, constituting 49% of the total, with the majority of purchases falling within the technology category